185k views
3 votes
How do I solve -1/3y-6=-11

User Parobay
by
5.3k points

2 Answers

2 votes

Answer:

Explanation:

-1/3y - 6 = -11

-1/3y - 6 + 6 = -11 + 6

-1/3y = -5

-1/3y * 3y = -5 * 3y

-1 = -15y

-1 / -15 = -15y / -15y

y = 1/15

User TrebledJ
by
5.0k points
5 votes

For this case we must solve the following equation:


- \frac {1} {3}y-6 = -11

We add 6 to both sides of the equation:


- \frac {1} {3} y = -11 + 6\\- \frac {1} {3} y = -5

We multiply by 3 on both sides of the equation:


-y = 3 * (- 5)\\-y = -15

Finally we have:


y = 15

Answer:


y = 15

User Noufal Kmc
by
5.9k points